The Design and Experiments on Corner Reflectors for Urban Ground Deformation Monitoring in Hong Kong - Yuxiao Qin; Daniele Perissin; Ling Lei (International Journal of Antennas and Propagation)
PSInSAR technology has been proved to be a powerful tool for monitoring urban ground displacement information to a millimetric accuracy. When it comes to the validation of PS-derived ground deformation, artificial corner reflector (CR) can be very useful due to its relative stability and high signal-to-noise ratio (SNR). In this paper, we will evaluate some general criteria for designing and setting up corner reflectors, including the shape, size, material, location, and others. An ideal prototype known as the rectangular trihedral with special designs is brought up in this paper, and validation experiments were conducted in Hong Kong to demonstrate the ability of the proposed prototype. The field data agreed with theoretical analysis, bringing up an economical and applicable approach for CR application in urban ground deformation monitoring.